Boundary effects in a quasi-two-dimensional driven granular fluid - Smith, Nathan D.; Smith, Mike I. (American Physical Society, 2017)
The effect of a confining boundary on the spatial variations in granular temperature of a driven quasi-2d layer of particles is investigated experimentally. The radial drop in the relative granular temperature ΔT/T, exhibits a maximum at intermediate particle numbers which coincides with a crossover from kinetic to collisional transport of energy. It is also found that at low particle numbers, the distributions of radial velocities are increasingly asymmetric as one approaches the boundary. The radial and tangential granular temperatures split, and in the tails of the radial velocity distribution there is a higher population of fast moving particles travelling away rather than towards the boundary.